The Art: a bridge to learning in small schools - Coppi, Antonella (Formazione & insegnamento, 2020)
«Multi-classes shall consist of not less than 8 and not more than 18 pupils». This appears in the article 10, paragraph n.1, Dpr n. 81 - 2009: Rules for the reorganization of the school network and the rational and effective use of human resources of the school. A recent research, promoted by INDIRE, revealed the existence of a varied universe of small schools in our country. Through a quali-quantitative approach for the representation of the phenomenon, a population of reference was identified, together with the detection of the features of the local territories in which said schools are located. Relevant results demonstrate how the needs of the territory, related to both contexts and groups, can give rise to significant experiences in terms of pedagogically innovative learning through art-related activities. This contribution reports the main line of a teaching of a bilingualism Project in South Tyrol, through different arts expression applicable to the context of small South Tyrolean mountain schools.